Genome-Wide Identification and Expression Pattern Analysis of the HAK/KUP/KT Gene Family of Cotton in Fiber Development and Under Stresses - Yang, Xu; Zhang, Jingjing; Wu, Aimin; Wei, Hengling; Fu, Xiaokang; Tian, Miaomiao; Ma, Liang; Lu, Jianhua; Wang, Hantao; Yu, Shuxun (Frontiers in Genetics, 2020)
The potassium transporter family HAK/KUP/KT is a large group of proteins important in plant potassium transport and plays a crucial role in plant growth and development, especially in economic crops. Although HAK/KUP/KT genes have been identified in many species, research on these genes is still quite rare in cotton. In this study, a total of 21, 24, 45 and 44 HAK/KUP/KT genes were identified in Gossypium arboreum, G. raimondii, G. hirsutum and G. barbadense, respectively. Phylogenetic analysis showed that these genes were divided into four clusters. The G. hirsutum gene promoters contained diverse cis-regulatory elements, such as drought-responsive elements, low-temperature-responsive elements and some other elements. The RNA-seq data and qRT-PCR results showed that HAK/KUP/KT genes had different expression patterns in fiber development. The qRT-PCR results of drought and NaCl treatment indicated that HAK/KUP/KT genes might play important roles in abiotic stress response. These results will provide molecular insights into potassium transporter research in cotton.